Development Implications of Arsenic in Drinking Water in Bangladesh - Murshid, Sharmeen (Water Nepal, 2003)
In Bangladesh the contamination of groundwater sources of drinking water with arsenic can be attributed to be the failure of the development approach in the water sector. Water agencies were unable to ensure the quality of drinking water, and the resulting arsenic contamination threatens the health of almost 85 million people. Arsenic levels in tubewells remained untested for decades and one out of 10 Bangladeshis may face a cancer-related death in the next 10 years. This outcome can be attributed to the indifference of aid-driven development approaches to local realities. Traditional ways of collecting water have been displaced by modern ways with negative effects. The arsenic problem raises questions not only about a particular technological device for extracting groundwater but also about the larger governance regime making decisions. By making international aid transparent and accountable at local and global levels, such problems can be avoided.Water Nepal Vol. Vol.9-10, No.1-2, 2003, pp.303-311